Models of Mental Health Triage for Individuals Coming to the Attention of the Police Who May Be Experiencing Mental Health Crisis: A Scoping Review. (9th May 2019) - Park, Alice; Booth, Alison; Parker, Adwoa J; Scantlebury, Arabella; Wright, Kath; Webber, Martin
Abstract: Police routinely encounter individuals experiencing mental distress, despite being ill-equipped to do so. Mental health triage aims to address these concerns. A range of approaches to triage has been introduced; however, no overview exists. We conducted a systematic scoping review of mental health triage co-responding schemes. Eleven databases were searched to identify the literature; each scheme was charted and described. Thirty-three studies describing 47 schemes were included. Intervention details were generally poorly reported, however, differences in personnel, training and information sharing were identified. There are multiple schemes in practice based on the co-responding model. Robust research into the cost and effectiveness of mental health triage is needed.